Efektivitas Manajemen Organisasi Pelayanan Publik pada Perencanaan dan Pengawasan Pembangunan Daerah B - Prayitno, Dedi (Jurnal Bisnis, Manajemen, dan Akuntansi, 2024)
Village Community Empowerment (LPMK) is an independent community social institution as a forum for participation by residents and Village partners to realize the aspirations of community needs in the field of development. The implementation of Musrenbang must be carried out by supporting efforts to prevent corruption, so that it is hoped that the targets in the focus of State Finance can be achieved well. After presenting the results of the research and discussing them, it can be concluded that the Musrenbang process has been running with fairly good community involvement. Even though the Musrenbang is already quite large, namely approximately 50% - 70%, efforts are still needed to increase the role of RT, RW and LPMK in area B in the Musrenbang process. Pramusrembang needs to involve mass organizations/institutions/associations and business actors in the region as a form of regional cooperation and a form of channeling to complement the realization of physical/non-physical activities that cannot be handled by budget implementers from Regional Apparatus Organizations (OPD). Campus